Application of Chaos Optimization Algorithm to Nonlinear Constrained Programming - Zhiliang Wang; Yongshan Zhang (2010 International Conference on E-Product E-Service and E-Entertainment, 2010)
The studying history and present situation of chaos optimization algorithm is summarized and the basic steps of this method are introduced. A new, feasible chaos optimization is presented to nonlinear constrained programming problems. Computing results in an instance show that this algorithm is reliable and applicable to almost all of the problems in multidimensional, nonlinear, complex constrained programming. This algorithm is liable to be applied and mastered.